Responsibility Of The Elderly In Upbringing - Turgunova Aziza Tashpulatovna (Peerian Journals Publishing, 2024)
This article focuses on the rich instructive life experience, practical knowledge, experience and skills of the socially active older generation, the status of old age in society and families and the scientific and methodological directions of the development of the system of education in students based on modern gerontopedagogical approaches.
Keywords: pedagogy; education; people; culture